Jews and Christians - parting ways in the first two centuries CE?: reflections on the gains and losses of a model - Schröter, Jens; Edsall, Benjamin A.; Verheyden, Joseph (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche / Beihefte, 2021)
Frontmatter -- Table of Contents -- Introduction -- From “Wide and Narrow Way” to “The Ways that Never Parted”? Road Metaphors in Models of Jewish-Christian Relations in Antiquity -- What Never Belonged Together Cannot Part: Rethinking the So-Called Parting of the Ways between Judaism and Christianity -- Ioudaismos, Christianismos and the Parting of the Ways -- Was Paul a Jew Within Judaism? The Apostle to the Gentiles and His Communities in Their Historical Context -- Matthew within or outside of Judaism? From the ‘Parting of the Ways’ Model to a Multifaceted Approach -- Character and Conflict: Who Parts Company in Acts? -- “John within Judaism?” Textual, Historical, and Hermeneutical Considerations -- The Epistle of Barnabas, Jews and Christians -- Justin Martyr without the “Parting” or the “Ways” -- Beyond “The Parting of the Ways” between Jews and Christians in Asia Minor to a Model of Variegated Interaction -- Living Apart Together: Jews and Christians in Second-Century Rome – Re-visiting Some of the Actors Involved -- Jews and Christians? Sketches from Second Century Alexandria -- List of Contributors -- Index of Ancient Sources -- Index of Modern Authors -- Index of Subjects